Apparent Solubility and Dissolution Profile at Non-Sink Conditions as Quality Improvement Tools - Petralito, Stefania; Zanardi, Iacopo; Memoli, Adriana; Annesini, M. Cristina; Millucci, Vincenzo; Travagli, Valter (IntechOpen, 2012)
None